Novel approach to enhance light absorption of porphyrin/graphene oxide composites by PH and concentration modification for energy applications. (August 2019) - Bajjou, O.; Bakour, A.; Khenfouch, M.; Baitoul, M.; Mothudi, B.; Maaza, M.; Faulques, E.
Abstract: Graphene oxide (GO) decorated with nanostructured porphyrin (PN) was synthesized and the interfacial interaction between these two components were investigated by using Scanning electron microscopy (SEM), X-ray, and UV-Visible absorption spectroscopy. These techniques showed good dispersion of GO and PN as well as a π-π intermolecular interaction confirming the energy/charge transfer. Moreover, X-ray diffraction study confirmed the intercalation of PN in GO and their disaggregation. The UV-Visible results showed an important interaction between GO and porphyrin nanorods under different pH values and concentrations resulting in the enhancement of optical absorption of GO-PN. The findings presented here are important to achieve the functionalization of graphene oxide with PN for various optoelectronic applications.